Teaching Vocabulary Through Advertisement at The First Grade Students of Vocational High School - Muhamad Sofian Hadi; Lidiyatul Izzah; Firdha Larasati (Universitas Cokroaminoto Palopo, 2021)
The objectives of study is to find out whether there is an improvement in students’ vocabulary mastery after using advertisement language to the first grade student of SMks Khazanah Kebajikan in academic year 2020/2021. The design research was pre-experimental research by giving pre-test, treatment, and post-test. The population of this research are the student of first grade of SMKs Khazanah Kebajikan in academic year 2020/2021. The sample of this research class of 10 AP. the value of t-calculation (3.97) was higher than the value of t-table (2.093) at the significance level 0.05, it can be concluded that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted (3.97>2.093). There is a significant difference between teaching vocabulary through advertisement and teaching vocabulary without Advertisement. Therefore, teaching vocabulary through Advertisement effectively enriches students' vocabulary mastery. The Advertisement significantly affects the students of 10th AP grade of SMKs Khazanah Kebajikan